The Political Economy of Deposit Insurance - Laeven, Luc (World Bank, Washington, D.C., 2013)
The author uses a political economy framework to analyze cross-country differences in deposit insurance coverage. He finds supporting evidence of the significance of private interest theories in explaining coverage of deposit insurance. Deposit insurance coverage is significantly higher in countries where poorly capitalized banks dominate the market and in countries where depositors are poorly educated. The author does not find that coverage is significantly related to political-institutional variables, such as the degree of democracy or restraints on the executive, or to proxies for the general level of institutional development, such as per capita income or property rights. These results provide evidence in support of the private interest view, according to which risky banks lobby for extensive coverage.